Huygens' dipole for polarization-controlled nanoscale light routing - Nechayev, Sergey; Eismann, Jörg; Neugebauer, Martin; Wozniak, Pawel; Bag, Ankan; Leuchs, Gerd; Banzer, Peter (Physical Review A, 2019)
Structured illumination allows for satisfying the first Kerker condition of in-phase perpendicular electric and magnetic dipole moments in any isotropic scatterer that supports electric and magnetic dipole resonances. The induced Huygens' dipole may be utilized for unidirectional coupling to waveguide modes that propagate transverse to the excitation beam. We study two configurations of a Huygens' dipole, longitudinal electric and transverse magnetic dipole moments or vice versa. We experimentally show that only the radially polarized emission of the first and azimuthally polarized emission of the second configuration are directional in the far field. This polarization selectivity implies that directional excitation of either transverse magnetic (TM) or transverse electric (TE) waveguide modes is possible. Applying this concept to a single dielectric nanoantenna excited with structured light, we are able to experimentally achieve scattering directivities of around 23 and 18 dB in TM and TE modes, respectively. This strong directivity paves the way for tunable polarization-controlled nanoscale light routing and applications in optical metrology, localization microscopy, and on-chip optical devices.
CRIS-Team WoS Importer:2019-04-30

Towards fully integrated photonic displacement sensors - Bag, Ankan; Neugebauer, Martin; Mick, Uwe; Christiansen, Silke; Schulz, Sebastian A.; Banzer, Peter (Nature Communications, 2020)
The field of optical metrology with its high precision position, rotation and wavefront sensors represents the basis for lithography and high resolution microscopy. However, the on-chip integration—a task highly relevant for future nanotechnological devices—necessitates the reduction of the spatial footprint of sensing schemes by the deployment of novel concepts. A promising route towards this goal is predicated on the controllable directional emission of the fundamentally smallest emitters of light, i.e., dipoles, as an indicator. Here we realize an integrated displacement sensor based on the directional emission of Huygens dipoles excited in an individual dipolar antenna. The position of the antenna relative to the excitation field determines its directional coupling into a six-way crossing of photonic crystal waveguides. In our experimental study supported by theoretical calculations, we demonstrate the first prototype of an integrated displacement sensor with a standard deviation of the position accuracy below λ/300 at room temperature and ambient conditions.
CRIS-Team Scopus Importer:2020-06-16